Multi-objective ship’s cargo handling model - Hess, Mirano; Hess, Svjetlana (Transport, 2015)
This paper proposes a new optimization model for ship’s cargo handling operations which solution gives the structure of cargo handling resources required, along with attaining the minimum total ‘in-port’ costs and the minimum of time required for completion of cargo operations. Due to complexity of the model which consists of composite multi-objective functions together with several decision variables and constraints, the solution has been sought by utilization of an adapted genetic algorithm combined with a hybrid algorithm. Testing of the model on real world data yielded acceptable results in a short time. In the course of decision making, the ship’s operator can, on the basis of the proposed model and taking into consideration shipping market data, choose appropriate variation of the returned solution, which incorporates minimum costs, minimum of operational time and related cargo handling resources. First published online: 22 May 2013